21.4k views
5 votes
Find the difference quotient

Find the difference quotient-example-1
User Olivrg
by
6.9k points

1 Answer

1 vote

Answer:


\large\boxed{(f(x+h)-f(x))/(h)=4x+2h}

Explanation:


f(x)=2x^2+4\\\\f(x+h)=2(x+h)^2+4\qquad\text{use}\ (a+b)^2=a^2+2ab+b^2\\\\f(x+h)=2(x^2+2xh+h^2)+4\qquad\text{use the distributive property}\\\\f(x+h)=2x^2+4xh+2h^2+4\\\\\text{Substitute to}\ (f(x+h)-f(x))/(h)\\\\(f(x+h)-f(x))/(h)=(2x^2+4xh+2h^2+4-(2x^2+4))/(h)\\\\(f(x+h)-f(x))/(h)=(2x^2+4xh+2h^2+4-2x^2-4)/(h)\\\\\text{combine like terms}\\\\(f(x+h)-f(x))/(h)=(4xh+2h^2)/(h)\qquad\text{distribute}\\\\(f(x+h)-f(x))/(h)=(h(4x+2h))/(h)\qquad\text{cancel}\ h


(f(x+h)-f(x))/(h)=4x+2h

User NetAction
by
5.6k points